Research evaluation down under: An outsider's view from the inside of the Australian approach - Bloch, Harry (Wiley-Blackwell Publishing, Inc., 2010)
Australia is currently undertaking its first national evaluation of university research, which is being performed by the Australian Research Council (ARC) at the request of the Australian government. The Australian approach to evaluation has some unique characteristics, especially a focus on evaluating research quantity and quality by the field of the research activity rather than by individual academic or administrative unit. This raises issues of the classification of areas of research, which has already caused controversy for Australian heterodox economists. There is also controversy about the quality rankings of economics journals. This paper provides a critical review of the Australian approach to research evaluation and discusses the implications for heterodox economists.